Edukasi Penggunaan dan Identifikasi Bahan Pengawet pada Produk Pangan di Manunggal Jaya Kecamatan Tenggarong Seberang - Febrina Mahmudah; Sabaniah Indjar Gama; Junaiddin (Fakultas Kehutanan dan Lingkungan Tropis, Universitas Mulawarman, 2023)
Food preservatives have been used in general by the public. The addition of food preservatives intends and intends to prevent the growth of spoilage bacteria in materials and products. The use of preservatives must be in small quantities or within the acceptable threshold. If the amount of preservatives used exceeds the threshold limit, it can trigger health problems. However, many producers abuse the addition of toxic preservatives, which are still found in food, so it is necessary to provide education and practice on detecting preservatives in food in the community, especially in Manunggal Jaya Village, Tenggarong opposite District. This activity begins with outreach and counseling about the types of preservatives and continues with analyzing the detection of dangerous preservatives in food products. The activity results show that the importance of education on preservatives in food products can increase the knowledge and understanding of the community in Manunggal Jaya Village, Tenggarong opposite District, and be able to carry out analyses using a simple method of detecting dangerous preservatives such as formaldehyde and borax.